The impact of international proceedings for bypassing the State: the example of Madagascar - (:unkn) unknown (My University, 2017)
Madagascar was severely hit by a protracted political and diplomatic crisis triggered by the 2009 military coup. The transitional government, in power until 2014, was unable to prevent the State from being bypassed and its humanitarian sovereignty from being transferred to international actors. This has done nothing to improve the situation of a country which is among the world's Least Advanced, ranked the third most vulnerable to climate hazards, behind Bangladesh and India (and the first in Africa) and the second most food-insecure in 2014. Christiane Rafidinarivo explains the mechanisms put in place by these actors between 2009 and 2014, and which are still applied today. She provides a comparative analysis in order to draw political and diplomatic lessons for African countries… he transitional crisis realism invented for Madagascar created an international precedent in humanitarian diplomacy, especially for Africa.
Keywords: African Research